Konsistensi Ideologi Pendidikan Agama Islam Di Tengah Perubahan Kurikulum Pendidikan Di Indonesia - Muhammad Zamroji (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2021)
Islamic education ideology is a systemic concept based on the Koran, al-Hadith, and ijtihad which aims for the happiness of human life in this world and the hereafter. The curriculum includes material from religious studies (aqidah, syari’ah, and morals) as well as general subjects such as mathematics. The methods used are classical and modern methods. Meanwhile, conservative educational ideology places more emphasis on conventional teachings which assume that everything humans do is God's will. The curriculum places more emphasis on moral aspects and the methods used also tend to be conventional, such as lectures. This is different from the ideology of liberal education which prioritizes individual freedom to develop educational concepts. The curriculum places more emphasis on practical matters and the teaching methods are free to suit individual wishes